Criopreservação de espécies frutíferas tropicais - Santana, Fernanda Vieira (2018)
Brazil has the greatest biodiversity in the world and presents favorable conditions for the cultivation of several species, such as climate and fertile soils. The conservation of plant genetic resources of both native and exotic species, in some cases, has been treated as a priority action in several research institutions. Coconut and mangaba tree are examples of fruit species of economic potential due to the extensive usage possibility of their fruits. Both in natura or industrialized products can be consumed, providing a variety of products used mainly in human food and in the pharmaceutical and/or cosmetics industry. Especially in the Northeast, these fruit trees represent a source of income for families that rely on the sustainable agriculture or the extractive activity. They are recalcitrant species, and the conservation of their genetic resources is based, mainly, on field collections since they do not tolerate the dehydration necessary for storage at low temperatures. In this sense, the application of cryopreservation techniques works as an alternative to the existing conservation methods. The process consists of conserving the plant material at an ultra-low temperature in liquid nitrogen, at -196 ºC. At this temperature, all activities are paralyzed, such as cell division and metabolic reactions, allowing the storage of the plant material for longer periods and the conservation of the existing genetic variability. The objective of this work was to improve the technical-scientific knowledge for the conservation of coconut and mangaba tree explants using cryopreservation techniques.